2019
DOI: 10.1103/physreve.99.023003
|View full text |Cite
|
Sign up to set email alerts
|

Theory for the density of interacting quasilocalized modes in amorphous solids

Abstract: Quasi-localised modes appear in the vibrational spectrum of amorphous solids at low-frequency. Though never formalised, these modes are believed to have a close relationship with other important local excitations, including shear transformations and two-level systems. We provide a theory for their frequency density, DL(ω) ∼ ω α , that establishes this link for systems at zero temperature under quasi-static loading. It predicts two regimes depending on the density of shear transformations P (x) ∼ x θ (with x th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
50
2
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 40 publications
(57 citation statements)
references
References 45 publications
4
50
2
1
Order By: Relevance
“…At finite γ the relation τ 3 ∼ ω 3 must break down, because destabilizing cubic modes' thirdorder coefficients τ 3 were shown to remain constant upon approaching the instability strain [24], whereas their frequency vanishes. Moreover, it was recently shown that under shear, D(ω) ∼ ω 4 does not always hold, but instead an exponent smaller than 4 is observed for well-annealed glasses [63]. This is consistent with recent numerical investigations which have highlighted a non-monotonic behavior of θ as a function of γ.…”
Section: Discussion and Outlooksupporting
confidence: 87%
See 1 more Smart Citation
“…At finite γ the relation τ 3 ∼ ω 3 must break down, because destabilizing cubic modes' thirdorder coefficients τ 3 were shown to remain constant upon approaching the instability strain [24], whereas their frequency vanishes. Moreover, it was recently shown that under shear, D(ω) ∼ ω 4 does not always hold, but instead an exponent smaller than 4 is observed for well-annealed glasses [63]. This is consistent with recent numerical investigations which have highlighted a non-monotonic behavior of θ as a function of γ.…”
Section: Discussion and Outlooksupporting
confidence: 87%
“…This is consistent with recent numerical investigations which have highlighted a non-monotonic behavior of θ as a function of γ. In particular, it was shown that θ first decreases as a function of γ, before increasing again upon approaching the yielding transition, and finally reaching a plateau value θ ≈ 1/2 in the steady state regime [55,58,63]. Furthermore, it was reported that the decrease of θ at intermediate strain is protocol-dependent and is significantly stronger for better-annealed glasses [58,62].…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…It is interesting to note that the range of variability observed in Fig. 4, Right appears to be consistent with a very recent study (61) of the depletion of tunneling two-level systems in stable computer glasses, possibly indicating that a subset of the QLMs is associated with tunneling two-level systems (1,2,36,62).…”
Section: Estimating Qlms' Frequency Scale By Pinching a Glasssupporting
confidence: 88%
“…Several other non-mean-field models [22,23] and phenomenological theories [1,[24][25][26] were previously put forward to the same aim; most of them, however, require parameter fine-tuning [22][23][24]26] or some rather strong a priori assumptions [1]. In addition, several other mean-field models, introduced in order to explain the low-frequency spectra of structural glasses, predict D(ω) ∼ ω 2 , independently of spatial dimension [16,[39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…Yet, despite previous efforts [1,[22][23][24][25][26], we currently lack insight into the origin of QLMs' statistical-mechanical properties. Moreover, recent progress in studying computer glass-formers revealed intriguing properties of QLMs [17,18,27], e.g.…”
Section: Introductionmentioning
confidence: 99%